تحديات الأسرة الصومالية في كندا وعلاجها في ضوء مقاصد الشريعة الإسلامية : دراسة فقهية ميدانية - ينديد، حليمة محمود عثمان (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2020)
The study analyzes the challenges of Somali families in Canada, and how to resolve them in the light of the Islamic Divine law (Maqaṣid al-Shariʻah al-Ḥanif) through an analytical field study. The study aims with a critical approach, to present, diagnose and analyze the social, educational, economic and legal challenges facing Somali families in their new country, Canada. These challenges are related to preserving the family structure and the purpose of marriage in Islam which controls the legitimate rights of spouses, the management of family affairs as well as raising or educating the young generation in accordance with the Islamic teachings. The study includes two major themes: first, the study illustrates the current social, educational, economic and legal aspects of living in Canada for Somalis. The data on this was collected through questionnaire and survey of selected study group of Somali Canadians. Secondly, the study identifies the challenges of the Somali families in Canada in their new home and the solutions of such challenges through and within the aims of the Islamic Divine law (Maqaṣid al-Shariʻah al-Ḥanif). The study discovers that the magnitude of the impact of environmental challenges on the family is eloquent of family cohesion; as harmony and cooperation between spouses decrease, conflict and frequent divorce among Somali Canadian Families begin to occur which in turn are carried over to the second generation. Addressing this depressing state of the Canadian Somali family requires recourse through the jurisprudence of Muslim minorities (Fiqh al-Aqalliyat) and within the higher aims of the Islamic Divine law, as well as consolidated efforts of the Somali community including scholars, parents and youth to overcome these challenges and preserve their cultural and religious identity.